Implementation of Academic Supervision of Teacher Performance in Online Learning during the Covid-19 Pandemic (Case Study of Public Elementary Schools in Wonosegoro, Boyolali) - Natami, Harindra Dina; Murtiyasa, Budi; Sutama, Sutama (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Supervision is required in every institution to control and maintain its quality, including educational institutions. Therefore, academic supervision must be carried out in educational institutions to ensure learning inputs and outputs. This research was a case study qualitative research with analysis techniques of interactive data. The sample in this study was 12 respondents of school principals in Wonosegoro District, Boyolali, obtained by using the proportional sample technique. Data collection techniques included interviews, observations, and questionnaires. The validity of the data employed triangulation techniques. This study aimed to observe the implementation of academic supervision during the COVID-19 pandemic at Public Elementary Schools in Wonosegoro, Boyolali. The results showed that; 1) Some schools have not been prepared appropriately in the implementation of academic supervision; 2) The implementation of academic supervision only used interviews via WhatsApp groups; 3) In the evaluation of supervision: some teachers were still constrained by the use of technology in implementing online learning, some teachers were less creative in choosing learning media, and the implementation of learning was not entirely following the learning design; 4) In follow-up academic supervision: teachers performance coaching was by the principals. The results of academic supervision are applied as a guide for reflection in improving teacher performance.